Evaluation of the Use of Antibiotics in Chronic Renal Failure Patients in RSUP Dr. Soeradji Tirtonegoro Klaten Period 2014 - Pradina, Gita Ayu; Cholisoh, Zakky (Universitas Muhammadiyah Surakarta, 2017)
Antibiotics are one of the most widely used drugs in curing various kinds of infectious diseases. The use ofantibiotics, especially in chronic renal failure, need to be considered because it can cause nephrotoxicityin kidneys. The purpose of this study was to evaluate the rational use of antibiotics in RSUP Dr. SoeradjiTirtonegoro in cases of chronic renal failure in 2014. The evaluation includes the right indication, theright drug, right patient, and proper dosage. This research is conducted in a manner that is based on aretrospective medical record belongs to chronic renal failure patients on inpatient RSUP Dr. TirtonegoroKlaten 2014. The search results obtained from medical records and evaluation results indicated the useof appropriate antibiotics as many as 20 cases (55.56%), patients with chronic renal failure who meet theappropriate criteria are 39 cases (97.7%), use of the right type of antibiotics drugs there were 13 cases(29,5%), and to use appropriate antibiotics doses were 21 cases (47.7%). Discharge status of patientswith a total of 36 cases (100%) with result of the patient’s health improved. From the result of arithmeticleukocytes figure, there are 33 cases ( 91.67 % ) with leukocytes count back to normal.